2008
DOI: 10.1016/j.ultsonch.2007.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous extraction of epimedin A, B, C and icariin from Herba Epimedii by ultrasonic technique

Abstract: An ultrasonic-assisted extraction (UAE) procedure of epimedin A, epimedin B, epimedin C and icariin from Herba Epimedii was developed. The effects of ethanol concentration, ratio of liquid to solid, UAE time, extraction temperature and number of extraction cycles on the extraction yields of the four flavonoids from Herba Epimedii were investigated. The optimal UAE condition was found using orthogonal test: 50% (v/v) ethanol solution, liquid:solid ratio of 30 ml/g, ultrasonication duration 30 min, extraction te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 21 publications
1
52
0
Order By: Relevance
“…The standard rutin treated with the same irradiation also showed the same strong capacity of absorbing ultraviolet and unchanged UV spectra (data not shown). Some flavonoids (epimedin A, B, C and icariin) were degraded (concentrations decreased) under the UV irradiation according to the decreasing absorbance [15], while the absorbance of rutin increased under the same treatment in this study. So it may be deduced that not all the flavonoids showed the abilities of anti-UV, and that whether the UV absorbance of flavonoids under long-time UV irradiation could be used for concentration determination needed further validation.…”
Section: Ability Of Uv Absorption Of the Main Flavonoidmentioning
confidence: 50%
See 2 more Smart Citations
“…The standard rutin treated with the same irradiation also showed the same strong capacity of absorbing ultraviolet and unchanged UV spectra (data not shown). Some flavonoids (epimedin A, B, C and icariin) were degraded (concentrations decreased) under the UV irradiation according to the decreasing absorbance [15], while the absorbance of rutin increased under the same treatment in this study. So it may be deduced that not all the flavonoids showed the abilities of anti-UV, and that whether the UV absorbance of flavonoids under long-time UV irradiation could be used for concentration determination needed further validation.…”
Section: Ability Of Uv Absorption Of the Main Flavonoidmentioning
confidence: 50%
“…The variation in the abilities of UV absorption of different flavonoids (the purified rutin from the cultivated L. barbarum leaves and the epimedin A, B, C and icariin from Herba epidemii leaves [15]) indicated that not all the flavonoids showed the capacity of anti-UV, and that whether the UV absorbance of flavonoids under long-time UV irradiation could be used for concentration determination needed further validation. The mechanism for the UV absorption capacity of rutin and UV induced degradation of flavonoids as epimedin A, B, C and icariin needs further research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many new extraction technologies have been developed to separate flavonoids from plants (Dai & Mumper, 2010), such as ultrasound-assisted extraction (UAE) (Albu, Joyce, Paniwnyk, Lorimer, & Mason, 2004;Zhang, Yang, Li, & Wang, 2008), subcritical water extraction (SWE) (Jo et al, 2013;Matshediso, Cukrowska, & Chimuka, 2015), supercritical fluid extraction (SFE) (Maran, Manikandan, Priya, & Gurumoorthi, 2015), microwave-assisted extraction (MAE) (Rostagno, Palma, & Barroso, 2007). Subcritical extraction does not require an alternative energy source such as microwave and ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…The main bioactive components in E. brevicornum are epimedin epimedin A, epimedin B, epimedin C and icariin [7]. Recently, icariin (C 33 H 40 O 15 : molecular weight: 676.67) has been reported to have a variety of pharmacological actions, including antioxidant, anti-inflammatory, anti-depressant, anti-obesity, estrogen-like and immunoregulatory activities [8]. However, the effects of icariin on physical fatigue have not been investigated thus far.…”
Section: Introductionmentioning
confidence: 99%